Nutrition economic evaluation of a probiotic in the prevention of antibiotic-associated diarrhea - Lenoir-Wijnkoop, Irene; Nuijten, Mark J.; Craig, Joyce; Butler, Christopher C. (Frontiers in Pharmacology, 2014)
Introduction: Antibiotic-associated diarrhea (AAD) is common and frequently more severe in hospitalized elderly adults. It can lead to increased use of healthcare resources. We estimated the cost-effectiveness of a fermented milk (FM) with probiotic in preventing AAD and in particular Clostridium difficile-associated diarrhea (CDAD). Methods: Clinical effectiveness data and cost information were incorporated in a model to estimate the cost impact of administering a FM containing the probiotic Lactobacillus paracasei ssp paracasei CNCM I-1518 in a hospital setting. Preventing AAD by the consumption of the probiotic was compared to no preventive strategy. Results: The probiotic intervention to prevent AAD generated estimated mean cost savings of £339 per hospitalized patient over the age of 65 years and treated with antibiotics, compared to no preventive probiotic. Estimated cost savings were sensitive to variation in the incidence of AAD, and to the proportion of patients who develop non-severe/severe AAD. However, probiotics remained cost saving in all sensitivity analyses. Conclusion: Use of the fermented dairy drink containing the probiotic L. paracasei CNCM I-1518 to prevent AAD in older hospitalized patients treated with antibiotics could lead to substantial cost savings.